Effectiveness of Tpack-Based Learning on Student Learning Outcomes in Elementary Schools - Linatus Shofiyah (Green Publisher, 2024)
21st-century learning demands that teachers integrate communication and collaboration skills, along with the use of information technology, into a framework known as TPACK. The research method used is descriptive qualitative, and the data collection technique employed is interviews. The subjects of this research are teachers and sixth-grade students of SD Negeri Kalisabuk 03 Kesugihan, Cilacap Regency. There are seven components to TPACK that need to be understood: Technological Knowledge, Pedagogical Knowledge, Content Knowledge, Technological Pedagogical Knowledge, Technological Content Knowledge, Pedagogical Content Knowledge, and Technological Pedagogical Content Knowledge. This article aims to determine the effectiveness of TPACK-based learning on student learning outcomes in elementary schools. The results of this study indicate that TPACK-based learning is effective for elementary school education and can enhance student learning outcomes. Additionally, the implementation of TPACK-based learning in elementary schools for sixth-grade students shows that all students are enthusiastic and actively participate in the learning process.